1988
DOI: 10.1071/pp9880519
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Development in NaCl-Treated Plants. I. Leaf Na+ and Cl- Concentrations Do Not Determine Gas Exchange of Leaf Blades in Barley

Abstract: Plants of Hordeum vulgare cv. Clipper were grown in gravel culture in solutions containing 0, 100 or 175 mol m-3 NaCl from the seedling stage until anthesis. When salt was first applied, leaf 4 was elongating within the sheath, and leaf 7 had yet to appear on the growing apex. These two leaves were sampled most intensively. Relative to the controls, salinity reduced the final area of all leaves progressively with higher node of insertion, and in the 175 mol m-3 NaCl treatment the reduction was more than twice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 10 publications
3
26
1
1
Order By: Relevance
“…Similar results were found by Rivelli et al [39] for wheat grown at 150 mM NaCl for 30 d. The authors found that the greater effect on RGR occurred within the first 10 d of treatment, after which the difference between treatments largely disappeared. However, in an experiment with barley, the treatment differences in RGR were steady with time, over a 9-week period, RGR averaged 0.13, 0.09 and 0.09 for the 0, 100 and 175 mM NaCl treatments, respectively [40]. At the whole-plant level, decreases observed in RGR could be attributed to a photosynthetic response (ULR) and/or morphological changes (LAR), depending on the species [19].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found by Rivelli et al [39] for wheat grown at 150 mM NaCl for 30 d. The authors found that the greater effect on RGR occurred within the first 10 d of treatment, after which the difference between treatments largely disappeared. However, in an experiment with barley, the treatment differences in RGR were steady with time, over a 9-week period, RGR averaged 0.13, 0.09 and 0.09 for the 0, 100 and 175 mM NaCl treatments, respectively [40]. At the whole-plant level, decreases observed in RGR could be attributed to a photosynthetic response (ULR) and/or morphological changes (LAR), depending on the species [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although there can be strong correlations between increases in leaf ion concentrations and reductions in photosynthesis or stomatal conductance, there is as yet no unequivocal evidence for causal relationships. Correlations can disappear when considering different leaves, or different salinities (Rawson et al 1988a). Experiments using different genotypes differing in rates of Na + or Cl -accumulation may be able to distinguish between the effects of salt in the leaf, and salt in the soil.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the plant species and aim of the experiment, low, moderate or severe salt stress may be applied. Typically, we add salt twice daily (morning and evening), in 25 mM or 50 mM NaCl www.intechopen.com increments (Shavrukov et al, 2006(Shavrukov et al, , 2009(Shavrukov et al, , 2010a(Shavrukov et al, , 2010b, in agreement with other salinity research groups (Boyer et al, 2008;Dreccer et al, 2004;Forster et al, 1990Forster et al, , 1994Gorham, 1990;Munns & James, 2003;Rawson et al, 1988aRawson et al, , 1988bShah et al, 1987;Watson et al, 2001). We have found that suitable salt stress levels are typically 100-150 mM NaCl for bread wheat (Dreccer et al, 2004;Gorham et al, 1987;Munns & James, 2003;Shah et al, 1987), 150-200 mM NaCl for barley (Forster et al, 1990(Forster et al, , 1994Gorham et al, 1990;Rawson et al, 1988aRawson et al, , 1988bShavrukov et al, 2010a), and 250-300 mM NaCl for tolerant cereals such as wild emmer wheat, Triticum dicoccoides (Shavrukov et al, 2010b), and for saltbush, Atriplex ssp.…”
Section: Salinitymentioning
confidence: 62%
“…The simplest to use are quartz gravel or river sand, and both are widely used in such systems (Boyer et al, 2008;Dreccer et al, 2004;Greenway, 1962;Munns & James, 2003;Rawson et al, 1988aRawson et al, , 1988b. However, small quartz particles can easily block and damage the pumping system.…”
Section: Alternative Substrates For Supported Hydroponicsmentioning
confidence: 99%